REBRANDING TERMINAL GROGOL: WAJAH BARU TERMINAL GROGOL - Regan Vicgor Wijaya; Nafiah Solikhah (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
The terminal is well known to all Jakartans as a public facility for finding public transportation modes according to their destination. Public transportation such as city buses and angkots use the terminal as a starting point and take passengers to other terminals and stopping points. Judging from the current conditions, public transportation modes at the terminal are less in demand as a result of technological developments in the transportation sector which make it easier for them to use other modes of transportation, for example, online taxis. This causes functional degradation at the terminal which can slowly disappear. The degradation that occurs in the terminal then has an impact on the environment which also becomes quieter and "dead". One of the terminals that has experienced the impact of this development is the Grogol Terminal. The narrow and elongated shape of Grogol Terminal also allows for congestion due to buses and angkots. This can be a source of air pollution for the surrounding environment because Grogol Terminal also lacks green space. This design is proposed with the Urban Acupuncture approach, namely utilizing points in cities that are less active to revive the surrounding environment and the Biophilic Architecture approach to create a healthy environment. The results obtained through this design are to bring out a new face for Grogol Terminal and maximize the potential of facilities at Grogol Terminal as a transit point. Keywords:  biophilic architecture; degradation; environment; facilities; Grogol terminal; urban acupuncture Abstrak Terminal sudah dikenal oleh semua masyarakat Jakarta sebagai fasilitas publik untuk mencari moda transportasi umum sesuai titik tujuannya. Angkutan umum seperti bus kota dan angkot menjadikan terminal sebagai tempat pangkal dan mengantar penumpang menuju terminal dan titik perhentian lain. Melihat dari kondisi yang berlangsung, moda transportasi umum di terminal berkurang peminatnya sebagai dampak dari perkembangan teknologi di bidang transportasi yang memudahkan mereka untuk menggunakan moda transportasi lainnya sebagai contoh ojek online. Hal ini menimbulkan degradasi fungsi pada terminal yang perlahan-lahan dapat menghilang. Degradasi yang terjadi pada terminal kemudian berdampak pada lingkungannya yang juga menjadi lebih sepi dan “mati”. Salah satu terminal yang telah mengalami dampak dari perkembangan tersebut adalah Terminal Grogol. Bentuk lahan Terminal Grogol yang sempit dan memanjang juga memungkinkan terjadinya kepadatan akibat bus dan angkot. Hal ini dapat menjadi sumber polusi udara bagi lingkungan sekitarnya karena Terminal Grogol juga minim ruang hijau. Perancangan ini diusulkan dengan pendekatan Akupunktur Perkotaan yaitu memanfaatkan titik pada kota yang kurang aktif untuk menghidupkan lingkungan sekitarnya dan pendekatan Arsitektur Biofilik untuk menciptakan lingkungan yang sehat. Hasil yang diperoleh melalui perancangan ini adalah memunculkan wajah baru dari Terminal Grogol serta memaksimalkan potensi fasilitas pada Terminal Grogol sebagai titik transit.